Skilling Up Vietnam : Preparing the Workforce for a Modern Market Economy - Bodewig, Christian; Badiani-Magnusson, Reena; Macdonald, Kevin; Newhouse, David; Rutkowski, Jan (Washington, DC: World Bank, 2014)
Education has played an important role in making Vietnam a development success story over the last 20 years. In the 1990s and early 2000s Vietnam experienced rapid economic growth. The accelerated growth was driven predominantly by productivity increases that came in the wake of a rapid shift of employment from low-productivity agriculture to higher-productivity nonfarm jobs. Vietnam's economy began to industrialize and modernize. Poverty fell dramatically. And education played an enabling role. Vietnam's committed effort to promote access to primary education for all and to ensure its quality through centrally set minimum quality standards has contributed to the country's reputation for having a young, well-educated workforce. Results from the 2012 Program for International Student Assessment (PISA) and new evidence from an adult skills survey presented in this book show that literacy and numeracy among Vietnam's youth and young urban adult workforce are strong and exceed those of even some wealthier countries. Despite its clear progress, Vietnam is facing new challenges. The pace of economic growth and the reallocation of jobs away from agriculture have slowed in recent years. Rather than productivity improvements, capital investments have become the main source of economic growth, but this model is not sustainable for ensuring continued rapid economic growth. The size of its workforce is still expanding, but its youth population is shrinking, which means that Vietnam cannot continue to rely on the size of its workforce for continued success. Instead, it needs to focus on making its workforce more productive and on alleviating skills barriers to labor mobility.